PERLINDUNGAN HUKUM TERHADAP PEMBELI ATAS TANAH YANG TELAH DITANDATANGANI PERJANJIAN PENGIKATAN JUAL BELI (PPJB) DAN DIJUAL KEMBALI OLEH DEVELOPER - Arrahman Hijratul Islami Tobing; Putra Hutomo; Furcony Putri (INTELIGENSIA MEDIA, 2025)
PPJB is made as a preliminary agreement made by the seller and buyer in the sale and purchase of land rights because there are conditions that have not been fulfilled by one of the parties, so the sale and purchase before the PPAT cannot be carried out, so the prospective buyer seller first makes a PPJB before a Notary as a Public Official. The problem formulations in this research are: 1) What is the legal effect of the Sale and Purchase Binding Agreement on land acquired by the buyer and resold by the developer?; 2). How is the legal protection of the buyer of the land based on the Sale and Purchase Binding Agreement (PPJB) of the land that has been paid in full and resold by the developer? By using the theory of legal protection according to Satjipto Rahardjo and the theory of legal consequences according to R. Soeroso, it can be concluded that the legal consequences of the Sale and Purchase Binding Agreement on the land obtained by the buyer and resold by the developer are very detrimental to the buyer who has done the PPJB before, and as promised can be said to have broken the promise (default) as stipulated in Article 1238 of the Civil Code.2) The legal protection obtained by the parties in terms of the transfer of land rights in the sale and purchase binding agreement is very strong because the proof of the sale and purchase binding agreement is made before an authorized public official in this case is a Notary, by signing the deed in front of a Notary or PPAT and then explaining its contents to the parties who make a sale and purchase binding agreement then signing before a Notary, the deed has valid and strong evidence as other authentic deeds.